REMINDER POLA HIDUP SEHAT SEBAGAI UPAYA PEMBERANTASAN MATA RANTAI SCABIES DI PESANTREN SA'ADATUDDAREN PROVINSI JAMBI - Haflin, Haflin; Agusriani, Agusriani; Hartesi, Barmi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
Sa'adatuddaren Islamic Boarding School is one of the oldest Islamic boarding schools in Jambi City, located on the banks of the Batanghari River. One of the facilities provided by Islamic boarding schools is dormitories. Based on the survey conducted, problems were found, especially in female student dormitories. The dormitories are not kept clean, rubbish is strewn about, and female students use the Batanghari river water directly for bathing, defecating and washing. This condition causes health problems such as scabies, diarrhea, and others. Scabies is a major health problem at the Sa'adatuddaren Islamic Boarding School, Jambi Province. This is disturbing for students and dormitory supervisors, because it is difficult to apply PHBS to teenage students, at this age someone tends to be unstable and cannot control clean and healthy living habits, several supporting factors such as the condition of the Islamic boarding school, the students' busy routine and being far from their parents. Adolescence is the right age to form good habits, therefore MTs students are targets for socialization. Reminders are a solution for teenagers to create a scabies-free Islamic boarding school environment. The method involves conducting outreach, collecting data on students affected by scabies, treating infected students and implementing PHBS using Reminder stickers. The results of the outreach were an increase in knowledge, understanding and perspective of students at the Sa'adatuddaren Islamic boarding school in Jambi Province regarding scurvy and a healthy environmental cleanliness.